Makna Hari Raya Corpus Christi: Menjawab Keraguan Bahwa Rupa Ekaristi Adalah Tubuh dan Darah Kristus - Irwan Irwan; Shelomita Selamat (STIKAS Santo Yohanes Salib Kalimantan Barat, 2025)
According to a survey in the United States conducted in 2019, only one-third of Catholics in the US agree with the Catholic Church that the Eucharist is the Body and Blood of Christ. Two-thirds do not believe in the Real Presence. They argue that the Eucharist is just a symbol, not really the Body and Blood of Christ, not Jesus Christ. This article seeks to answer doubts that the Eucharistic form (consecrated bread and wine) is the Body and Blood of Christ by reflecting on the meaning of the Feast of the Body and Blood of Christ (Corpus Christi). This article is important to overcome the crisis of faith that is weakening the Catholic Church. The method used in this article is a literature study.